Enhancing judicial efficiency to foster economic activity in Portugal - Jin, Yosuke (OECD Economics Department Working Papers, 2019)
A well-functioning justice system is indispensable to business activity and to a society as a whole. Judicial efficiency measured by trial length, one of the essential factors in the effectiveness of the justice system, ensures contract enforcement, which is the basis of market transactions. Judicial efficiency is closely associated with accessibility to judicial services and the certainty of judicial decisions, raising people's confidence. Portugal has undertaken numerous judicial reforms in the past, to the extent that it is difficult to disentangle and evaluate fully the effects of each reform. Overall, judicial efficiency remains weak, as reflected in the average trial length and bottlenecks in a number of courts. The data collection system, significantly developed as part of the reforms, can be more fully utilised for allocating court resources. The autonomy of the judicial council and court presidents can also be strengthened so that they can effectively manage resources. Individual judges can be better incentivised through performance-oriented evaluation. Competition in the legal profession sector can be enhanced while increasing the transparency of legal services. Also, alternative dispute resolution mechanisms can be developed further, meeting different needs for judicial services, in particular those on insolvency, while alleviating court congestion. Finally, building on past and ongoing reform efforts, the judicial system should continue to improve the capacity to undertake forensic investigations of economic and financial crimes. This Working Paper relates to the 2018 OECD Economic Survey of Portugal (http://www.oecd.org/economy/portugal-economic-snapshot/)